Effect of Diameter, Root Moisture Content, Gauge Length and Loading Rate on Tensile Strength of Plant Roots and Their Contribution to Slope Stability - Damtew Tsige Melese (Lowland Technology International, 2021)
Root tensile strength is a crucial parameter for enhancement of soil shear resistance against failure. Mechanical stabilization of plant roots depends on the tensile strength properties of roots, friction properties, and root density and its network. The aim of the study is therefore, to conduct combined effect of various influential factors (diameter of the root, specimen length, testing speed, and root moisture variation) on the root tensile strength properties of plant roots. The root system of five selected plant species are studied. Intact and undamaged root specimens sampled and tested for root characteristics and tensile strength (Tr) at different root moisture content with different diameter classes. The result of the study further revealed that (a) testing speed has insignificant influence on plant root tensile strength (b) specimen length and plant root tensile strength showed a significant negative linear correlation (c) root diameter and tensile strength showed negative power function correlation (d) root moisture content had slightly negative correlation with root tensile strength. From five tested plant species, the highest tensile strength recorded in Salix subserrata followed by Eucalyptus globules. Therefore, Salix subserrata is a promising species for slope stabilization because of its root mechanical characteristics.